Diffusion of High Impact Educational Practices at a Saudi - Muhannad Almutiry; Mohammad Y. Alshehri; Gary Sayed (Athens Institute for Education and Research, 2022)
Higher education is challenged by workforce needs to transform its outcomes from "knowledge-based" to "competency-based" outcomes. High-impact educational practices, commonly referred to as HIPs, provide, among other benefits, efficacious development of workforce-ready specific competencies. Strategic implementation of HIPs has yet to be diffused at Saudi universities. The Northern Border University (NBU) has identified a set of core competencies graduate workforce-ready graduates. To effectively realize the intended outcomes of its core competencies, NBU selected a set of HIPs to increase student success. This paper discusses NBU's processes and implementation strategies in selecting core competencies and HIPs with ultimate aim of translating both to the local higher education culture and norms in order to effectively achieve desired outcomes.